DRIVING FACTORS OF INFORMATION TECHNOLOGY GOVERNANCE IN INDONESIAN BANKING SECTOR - Lee, Samuel David (UG Journal, 2020)
IT governance becomes the primary and integral part of successful implementation of corporate governance overall. IT governance must ensure the efficient an effective measure to increase the company’s business process. This study used the primary data with questionnaires. From 122 commercial banks in Indonesia and using purposive sampling that meets the criteria and completeness of the data are 33 banks as sample.Using multiple regression, the result of this study are: corpo rate performance appraisal and involvement of top management in IT were significant influenced the effectiveness of IT governance but corporate control was not significant. Banking sector as influenced by developing of IT should have committment to have ef fectiveness of IT Governance because it can increase your security of data and transaction, trust from your customer and performance of daily activities also.